Античні паремії в епістолярній спадщині Лесі Українки - Коваль-Гнатів, Дзвенислава; Koval-Hnativ, Dzvenyslava (Східноєвропейський національний університет імені Лесі Українки, 2016)
Досліджено латиномовні крилаті вислови в листах Лесі Українки, їхнє походження, часовий розвиток, уживання у творах античної літератури, в епістолярії письменниці, увагу акцентовано на значенні античних паремій і їх функціональності в її кореспонденції. We study a Latin winged expressions in letters of Lesіa Ukrainka, their origin, development in time, use in the works of ancient literature, in the author’s letters. The importance of ancient proverbs and their functionality in her correspondence is revealed. Epistolary heritage of Lesіa Ukrainka is not only an interesting and of informative source of the poet’s biography, but also a reflection of her literary works, poetic style. Latin winged expressions are evidence of creative thinking of a poet, revealing her identity in all its uniqueness and versatility which induce us to master the ancient languages and cultural heritage of antiquity.
Antique Paremias in Epistolary Heritage of Lesia Ukrainka
Keywords: паремії; епістолярій; крилаті вислови; пареміографія; антична міфологія; криптонім; першоджерело виразу; paremias; correspondence; winged expressions paremiology; ancient mythology; krypton; original expression